Quinolone resistance in Riemerella anatipestifer from Thai ducks: Mutation analysis of gyrA, parC, and plasmid-mediated quinolone resistance genes - Chutima Pathomchai-Umporn; Sudtisa Laopiem; Kriangkrai Witoonsatian; Sittinee Kulprasetsri; Pun Panomwan; Thaweesak Songserm; Nuananong Sinwat (Veterinary World)
Background and Aim: Riemerella anatipestifer is a Gram-negative bacterium causing systemic infections in ducks, often treated with quinolones. However, increasing resistance to quinolones poses a threat to effective treatment, and the molecular mechanisms underlying this resistance remain inadequately understood in Thailand. This study aimed to determine the minimum inhibitory concentrations (MICs) of nalidixic acid, ciprofloxacin, and enrofloxacin; identify mutations in the quinolone resistance-determining regions of gyrA and parC; and detect plasmid-mediated quinolone resistance (PMQR) genes in R. anatipestifer isolates from Thai ducks.